How opportunity costs decrease the probability of war in an incomplete information game - Solomon W. Polachek; Jun Xiang (Institute for the Study of Labor (IZA), 2008)
This paper shows that the opportunity costs resulting from economic interdependence decrease the equilibrium probability of war in an incomplete information game. This result is strongly consistent with existing empirical analyses of the inverse trade-conflict relationship, but is the opposite of the conclusion reached by Gartzke et al. (2001), who reject the opportunity cost argument in a game-theoretic framework. As a result of this paper's findings, one cannot dismiss the opportunity cost argument as the explanation why trading nations fight less. Instead this study reaffirms the central position of opportunity costs as the basis for the inverse trade-conflict relationship, thus implying that one need not rely on signaling.
urn:nbn:de:101:1-20081218105
Keywords: F10; 330; War; conflict; trade; trade-conflict relationship; interdependence; incomplete information game; signaling; Krieg; Politischer Konflikt; Opportunitätskosten; Internationale Wirtschaftsbeziehungen; Spieltheorie; Unvollkommene Information; Signalling; Theorie